Optimizing Coal Transfer Productivity at Taboneo: A Socio-Technical Analysis of STS Operations - Mohamad Nufel; Lili Purnamasita; Meilina Nurhasanah Hutagaol (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This qualitative study investigates the determinants of coal loading-unloading productivity at the Ship-to-Ship (STS) Transfer Taboneo in Indonesia. Through thematic analysis of interviews, observations, and documents involving crane operators, port managers, and ship crews, the research reveals a "Resilience through Informality" model. Findings indicate that high operational effectiveness is achieved not through optimal technical systems, but through the exceptional adaptive capacity and experiential knowledge of the workforce that compensates for significant vulnerabilities in equipment logistics and formal workflow systems. While this human-centric approach currently ensures operational continuity, it presents inherent fragilities related to workforce welfare, knowledge retention, and environmental compliance. The study concludes that sustainable productivity enhancement requires a dual strategy: formalizing existing tacit knowledge through competency-based frameworks while simultaneously strengthening technical and logistical infrastructures. This research contributes to maritime studies by highlighting the critical role of human capital in port efficiency and provides practical insights for developing sustainable port management strategies in resource-constrained environments.